Pijat Bayi Untuk Peningkatan Nafsu Makan Di Desa Oebola - Yurissetiowati Yurissetiowati (Pusat Riset dan Inovasi Nasional, 2023)
Children under five years old (toddlers) are an age group that is vulnerable to nutrition and health. At this time, the child's immune system is not strong enough to catch infectious diseases. In addition, children also often have bad eating habits, namely children often do not want to eat or have a decreased appetite, causing their nutritional status to decrease and their growth and development to be disrupted. One effort that can be done to increase a child's appetite is to do baby massage. Currently massage techniques have been widely used for health and weight gain in babies. This community service method is counseling and demonstration. The community service sample is 10 mothers and toddlers. The location is in the village of Oebola, Fatuleu District, Kupang Regency. The instruments used in this community service are leaflets, and demonstrations of baby massage for each toddler. The activity was carried out on November 20 2022 at 08.00 WITA with 2 sessions namely counseling and demonstrations. The results of community service showed an increase in the knowledge of toddler mothers from the majority (50%) having sufficient knowledge to the majority (50%) having good knowledge. For children's appetite also experienced an increase from initially almost all (80%) had less appetite to almost all (90%) had a good appetite. The conclusion from this community service activity is that the provision of health education about infant massage can increase the knowledge of toddler mothers and infant massage can increase the appetite of children aged 0-5 years.